Sejarah Idealisme di Tuban: Melacak Eksistensi Idealisme Islam Modernis Tahun 1474-1530 - Mukti, M Aziz (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2023)
Currently, studies relating to the Islamization process in Indonesia need to be increased in terms of quantity, this aims to support the development of the Islamization process that is currently taking place in Indonesia. At this stage studies related to the early history of the Islamization process in Indonesia are urgently needed, especially to provide enthusiasm and motivation for Muslims in Indonesia to always try to improve their Islam. This is due to the fact that when reflecting on history, the struggle of the Ulama at the beginning of the arrival of Islam in Indonesia was full of challenges, especially when the effective process of Islamization was carried out only when mixing several local traditions into the process of preaching, this caused a lot of cultural acculturation. In the development of several cultural acculturations by several groups it was considered that there were elements of khuparat or even heresy in it. Even so, at the beginning of the preaching of Islam, there were several groups of scholars who still tried to preach Islam by adhering to the principles of Shari'a and Aqeedah and only slightly incorporating elements of local traditions as an adaptive form which today is often also called the modernist group, as manifested in the application of syar'i tasawuf. In connection with the application of syar'i tasawuf, some evidence can be found which illustrates the application of syar'i tasawuf in several areas, such as one in Tuban Regency. Through this evidence, this research seeks to examine the existence of this Muslim group as a form of learning from the struggles of the Ulama in the early era of the arrival of Islam in Indonesia